Promoting the SDG Culture via Educational Strategies and Policies for Everyone (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of this present article is to investigate and evaluating the Strategy for Achieving Sustainable Development Goals (SDGs) in Indonesia as an Effort to Improve Quality Education. The method used in present study is qualitative-study approach or a descriptive-approach, with the basis of the discussion being the results of a literature study through multiple book sources, scientific articles from relevant journal sources, and the results of previous studies that are relevant to the topic at hand. This paper discusses the approach of the Sustainable Development Goals (SDGs) to enhance the quality of education in Indonesia, a developing nation with several challenges in the condition and quality of its education, which is not yet entirely sufficient and uniformly distributed. Then, consider the present condition of education and the government's involvement in overcoming barriers to increasing the quality of Indonesia’s education. It is envisaged that the establishment of the SDGs program would alleviate the issue of education's unequal distribution and increase its quality, therefore advancing the Indonesian country.